2011
DOI: 10.4184/asj.2011.5.4.228
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Minimally Invasive Transforaminal Lumbar Interbody Fusion for the Treatment of Spondylolisthesis and Degenerative Segmental Instability

Abstract: Study DesignThis is a retrospective case study.PurposeThis study was designed to analyze the surgical outcomes of patients who underwent minimally invasive transforaminal lumbar interbody fusion (TLIF) for the treatment of spondylolisthesis and degenerative segmental instability.Overview of LiteratureIf the surgical outcomes of a procedure are evaluated together with multiple indications, it is not clear how the procedure helped each subgroup of patients. For the reason that some indications achieve better out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 14 publications
2
20
0
7
Order By: Relevance
“…Значительная интраоперационная травма, а так-же относительно высокий риск развития ранних и отдаленных нежелательных последствий в виде ре-стеноза позвоночного канала, недостаточности формирования костного блока, образования ложно-го сустава ограничивают применение открытой транспедикулярной фиксации при начальных при-знаках сегментарной нестабильности [2,15]. Уста-новлена прямая корреляция объема резекции зад-них опорных элементов позвоночно-двигательного сегмента и развития послеоперационной нестабиль-ности при выполнении реконструкции позвоночно-го канала задним доступом [15,20,21].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Значительная интраоперационная травма, а так-же относительно высокий риск развития ранних и отдаленных нежелательных последствий в виде ре-стеноза позвоночного канала, недостаточности формирования костного блока, образования ложно-го сустава ограничивают применение открытой транспедикулярной фиксации при начальных при-знаках сегментарной нестабильности [2,15]. Уста-новлена прямая корреляция объема резекции зад-них опорных элементов позвоночно-двигательного сегмента и развития послеоперационной нестабиль-ности при выполнении реконструкции позвоночно-го канала задним доступом [15,20,21].…”
Section: Discussionunclassified
“…Уста-новлена прямая корреляция объема резекции зад-них опорных элементов позвоночно-двигательного сегмента и развития послеоперационной нестабиль-ности при выполнении реконструкции позвоночно-го канала задним доступом [15,20,21]. Кроме того, наличие незначительного дооперационного спон-дилолистеза, даже при очень малой хирургической агрессии в отношении элементов заднего опорного комплекса, например при фасетэктомии, вызывает прогрессирование спондилолистеза [22].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Because of a reduced destruction of the soft tissues, proponents of these MIS techniques claim to achieve superior clinical results with reduced postoperative pain, narcotic use, and hospital length of stay [4,5,10,12,16,23]. On the other hand, performing percutaneous instrumentation, fusion and decompression in complex cases with severe arthritic and stenotic changes could increase the complication rate and lower the accuracy of pedicle screw insertion [6].…”
Section: Discussionmentioning
confidence: 99%
“…6,24,26,38 A similar review of MI-TLIF studies suggests an infection rate of 0%-10%. 12,14,17,20,23,29,[35][36][37] O'Toole et al 16 found that the incidence of surgical wound infection was significantly lower after MI-TLIF (0.6%) than after open TLIF (4.0%); the decrease in the number of wound infections in that study was associated with a direct cost savings of $98,974 per 100 MI-TLIF procedures performed. 18 In our study, there was 1 surgical wound infection (0.2%), which compares favorably to other authors' experiences and may attest to the large volume and experience of the center.…”
Section: Infectionmentioning
confidence: 99%